A multi gene-approach genotyping method identifies 24 genetic clusters within the genotype II-European African swine fever viruses circulating from 2007 to 2022 - Gallardo, Carmina; Casado, Nadia; Soler, Alejandro; Djadjovski, Igor; Krivko, Laura; Madueño, Encarnación; Nieto, Raquel; Perez, Covadonga; Simon, Alicia; Ivanova, Emiliya; Donescu, Daniel; Milicevik, Vesna; et al. (Frontiers in Veterinary Science, 2023)
Introduction African swine fever (ASF) is a contagious viral disease of pigs and wild boar that poses a major threat to the global swine industry. The genotype II African swine fever virus (ASFV) entered the European Union (EU) in 2014 and since then fourteen countries have been affected, Italy and North Macedonia being the last in 2022. While whole genome sequencing remains the gold standard for the identification of new genetic markers, sequencing of multiple loci with significant variations could be used as a rapid and cost-effective alternative to track outbreaks and study disease evolution in endemic areas. Materials and methods To further our understanding of the epidemiology and spread of ASFV in Europe, 382 isolates collected during 2007 to 2022 were sequenced. The study was initially performed by sequencing the central variable region (CVR), the intergenic region (IGR) between the I73R and I329L genes and the O174L and K145R genes. For further discrimination, two new PCRs were designed to amplify the IGR between the 9R and 10R genes of the multigene family 505 (MGF505) and the IGR between the I329L and I215L genes. The sequences obtained were compared with genotype II isolates from Europe and Asia. Results The combination of the results obtained by sequencing these variable regions allowed to differentiate the European II-ASFV genotypes into 24 different groups. In addition, the SNP identified in the IGR I329L-I215L region, not previously described, grouped the viruses from North Macedonia that caused the 2022 outbreaks with viruses from Romania, Bulgaria, Serbia and Greece, differentiating from other genotype II isolates present in Europe and Asia. Furthermore, tandem repeat sequence (TRS) within the 9R-10R genes of the multigene family 505 (MGF505) revealed eight different variants circulating. Discussion These findings describe a new multi-gene approach sequencing method that can be used in routine genotyping to determine the origin of new introductions in ASF-free areas and track infection dynamics in endemic areas.